2020
DOI: 10.3390/ijms21217861
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of TLR4 in Circulating CD4+T Cells in Patients with Allergic Conjunctivitis and In Vitro Attenuation of Th2 Inflammatory Response by Alpha-MSH

Abstract: Ocular allergic diseases are frequently seen in ophthalmological clinical practice. Immunological damage is mediated by a local Th2 inflammatory microenvironment, accompanied by changes in circulating cell subsets, with more effector cells and fewer T regulatory cells (Tregs). This study aimed to evaluate the involvement of toll-like receptor 4 (TLR4) and α-melanocyte stimulating hormone (α-MSH) in the immune regulation associated with perennial allergic conjunctivitis (PAC). We performed an Ag-specific stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This therapeutic effect is mainly due to the increase in the Th1/Th2 ratio, the change in IgE and IgG2a antibody levels, and the reduction in mast-cell degranulation. In addition to the increase in the Th1/Th2 ratio, the increase in regulatory T cells (Tregs) and the epigenetic changes in T cells will also influence the effect of allergen-specific immunotherapy [ 30 ]. In order to understand the mechanism more deeply, it is necessary to further confirm the effect of allergen-loaded PLGA-PEG nanoparticles on effector T cells, Tregs, and epigenetic changes in T cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic effect is mainly due to the increase in the Th1/Th2 ratio, the change in IgE and IgG2a antibody levels, and the reduction in mast-cell degranulation. In addition to the increase in the Th1/Th2 ratio, the increase in regulatory T cells (Tregs) and the epigenetic changes in T cells will also influence the effect of allergen-specific immunotherapy [ 30 ]. In order to understand the mechanism more deeply, it is necessary to further confirm the effect of allergen-loaded PLGA-PEG nanoparticles on effector T cells, Tregs, and epigenetic changes in T cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that regulatory T cells can be generated in vitro by treating antigen-stimulated CD4 + T cells with a supplementation of α-MSH at the physiological concentration of 10 −11 M. The α-MSH-induced Tregs express CD25 and produce TGF-β, but not IL-4 [29,31,32]. In a recent study, α-MSH was also found in tears, and its concentration increased in perennial allergic conjunctivitis (PAC) patients compared with healthy participants [33].…”
Section: α-Msh Bioavailability In the Eyementioning
confidence: 99%
“…α-MSH is composed of 13 amino acids and is best known for its pigmentary effects in skin [ 28 ], but also has been indicated to exert anti-inflammatory and microbicidal effects discussed below [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Melanocortinsmentioning
confidence: 99%